THE PREACHING OF SUFI IN THE BATAK LAND DISTRICT OF SIMALUNGUN (A Study of Islamic Communication, Case Study of Tarekat Naqsyabandiyah Serambi Babussalam) - Efi Brata Madya; Moh Hatta Hatta; Syukur Kholil Kholil (State Islamic University of North Sumatra Indonesia, 2017)
This research aimed to know the history of development of the Sufi preaching of the Naqsyabandiyah Serambi Babussalam Simalungun, to find the concept of sufi preaching of Naqsyabandiyah Serambi Babussalam Simalungun, to analyze the form of Sufi preaching of Naqsyabandiyah Serambi Babussalam Simalungun, to find the typical communication form of the people of Naqsyabandiyah Serambi Babussalam Simalungun, and also to analyze the Success, opportunities and challenges of the future of sufi preaching of tarekat Naqsyabandiyah Serambi Babussalam Simalungun. Ingetting the data, it was conducted a series of interviews to the leader Tarekat Naqsyabandiyah Serambi Babussalam Simalungun, Dr. H. Ahmad Sabban Rajagukguk, MA, Nasir, as one of Syech H. Abdurrahman Rajagukguk’s friends, The founder of the tarekat, M. Sholahuddin Nasution, Ubaidillah, Dr. J. R. Saragih, The Regent of Simalungun, Drs. H. Amran Sinaga, Vice Regent of Simalungun, and other parties deemed relevant. The data were also obtained from participant observation, especially on the activities of Zikir and Suluk in the tarekat. Then analyzethe document to discover the history and development of the tarekat. Based on research, it was obtained the results that Sufi preaching has its own character. The followers of Tarekat Naqsyabandiyah Serambi Babussalam Simalungun convey the message of preaching through a real charity, especially in terms of the typical protruding behavior. Adopt nubuwah's attributes in terms of their interest in the aspects of the mundane. Although for further developments in the field of mysticism that gave rise to the neo-Sufism do not necessarily have to abandon the mundane. Even the neo-Sufism understands wealth or things that are mundanely can be utilized as much as possible for the benefit of preaching, social reform, and improvement of people. One interesting thing, both the early or neo-Sufism were still remain of Allah SWT. Both with the Sirryyah remaining or Jahriyah remaining in all occasions, whether at lying down, sitting, or standing, as a part attached to them. Similarly, the practice of Naqsyabandiyah Serambi Babussalam Simalungun led by Dr. H. Ahmad SabbanRajagukguk, MA